Research capability gaps hinder understanding of the impact of climate change on ecosystem services in the Latin American Pacific coast: Research capability and ecosystem services in Latin America - Calderon-Aguilera, Luis E. (HIDROBIOLÓGICA, 2022)
Background. Coastal communities are highly dependent on ecosystem services, but the benefits and livelihoods people derive from natural ecosystems are directly and indirectly affected by climate change. The need for a mechanistic understanding of how components of climate change translate into measurable impacts on ecosystems and society is fundamental to the ability to manage, plan and mitigate for the most likely environmental futures, yet progress in this area in tropical and subtropical countries is frustrated by a lack of research capacity at the local and regional level. Objectives. Here, we investigate the research capacity of the countries along the Pacific coast, between Mexico and Chile, a region with an extensive coastline (23,191 km) that spans 11 countries of varying socio-economic development status and anticipated to be especially vulnerable to climate change. Methods. Specifically, our focus was to explore how the effects of climate change on ecosystem services (provision, regulation and cultural) may relate to research capacity and gross domestic product (GDP) in each country along the Pacific coast of the Americas. Results. We find that, since 1980, the number of peer-reviewed scientific studies relevant to this topic strongly correlates with GDP (r = 0.90, p < 0.05) and that research effort is an order of magnitude lower along the Latin American Pacific coast (13.8 studies 1000 km-1) than in the neighbouring Californian coast (103 studies 1000 km-1). Conclusions. Our results highlight the need to better develop the research in the Latin America Pacific, and for more work on the key links between climate change and ecosystem services.